Analisis Kualitatif Pemanfaatan Data Usaha dalam Penguatan Keberlanjutan Ekonomi Masyarakat Desa di Kecamatan Tuntang - Ida Kusuma; Pranoto Pranoto (Universitas Kristen Indonesia Toraja, 2026)
This study analyzes the utilization of business data to strengthen the economic sustainability of rural communities in Tuntang District. A qualitative approach with a case study design was applied in 16 villages through in-depth interviews, participatory observation, and document analysis, while data analysis employed the Miles and Huberman model. The findings reveal that business data are strategically utilized to support evidence-based planning, mapping local economic potential, strengthening the capacity of Village-Owned Enterprises (BUMDes), and improving the digital literacy of business actors. The utilization of such data contributes to business growth, increased turnover, and improvements in bookkeeping, business planning, and access to formal sources of capital. In addition, business data also assist village governments in determining priorities for community economic empowerment programs more accurately and effectively. The main supporting factors include the commitment of village leadership, active participation of business actors, mentoring support, the availability of technological infrastructure, and a collaborative culture among stakeholders. Meanwhile, the challenges encountered include limited human resource capacity, infrastructure gaps, resistance from some business actors toward data transparency, and dependence on external assistance. This study formulates a participatory, integrated, collaborative, and sustainable business data utilization model as a contextual precision data-based approach to support rural economic development.